Initial results of a drug checking pilot program to detect fentanyl adulteration in a Canadian setting. (1st September 2018) - Tupper, Kenneth W.; McCrae, Karen; Garber, Ian; Lysyshyn, Mark; Wood, Evan
Highlights: Point-of-care drug checking was piloted in downtown Vancouver. Only 17.6% of "heroin" samples tested were found to contain the expected substance. Of 907 "heroin" samples tested, 90.6% tested positive for fentanyl. Of 256 "speed" samples tested, 5.9% tested positive for fentanyl. Abstract: Background: Opioid overdose deaths in North America have been rising largely as a result of fentanyl adulteration in the illegal drug supply. Drug checking is an established harm reduction intervention in some European settings but has not been broadly implemented or evaluated in North America. We are evaluating a pilot program offering drug checking for people who use street drugs in Vancouver, British Columbia. Methods: Drug checking services were implemented at two locations in Vancouver between November 2017 and April 2018 using a Fourier transform infrared (FTIR) spectrometer and fentanyl immunoassay strips. We report on the findings generated by this technological combination during the study period. Results: During the study period, a total of 1714 samples were tested. Of 907 samples expected to be heroin, only 160 (17.6%) contained the expected substance, and 822 (90.6%) tested positive for fentanyl. Of 256 samples expected to be speed or crystal meth, 225 (87.9%) contained amphetamine or methamphetamine, and 15 (5.9%) tested positive for fentanyl. The FTIR also found unexpected and potentially dangerous substances and adulterants other than fentanyl. Conclusions: This pilot program has demonstrated the feasibility of drug checking for identifying individual drug samples containing unexpected or hazardous substances, including fentanyl. By identifying the range of adulterants and diluents and giving an estimate of their prevalence in different drug types, it has also provided information about the composition of the illicit drug supply in an urban North American setting.